Modification of the cylindrical products outer surface influenced by radial beam of argon ions at automatic mode; Journal of Physics: Conference Series; Vol. 652 : Gas Discharge Plasmas and Their Applications (GDP 2015) - Valikov R. A. Roman Aleksandrovich; Yashin A. S. Aleksandr Sergeevich; Churkin S. A.; Yakutkina T. V. Tatjyana Viktorovna; Kalin B. A. Boris Aleksandrivich; Volkov N. V. Nikolay Viktorovich; Krivobokov V. P. Valery Pavlovich; Yanin S. N. Sergey Nikolaevich; Asainov O. Kh. Oleg Khaydarovich; Yuriev Yu. N. Yuri Nikolaevich (2015, 2015)
Title screen